2022
DOI: 10.55006/biolsciences.2022.2205
|View full text |Cite
|
Sign up to set email alerts
|

Review on phytochemical constituents and pharmacological activities of plant Calendula officinalis Linn

Abstract: Calendula officinalis, a member of the Asteraceae family and also called as Pot Marigold, is a fragrant herb used in Traditional Chinese Medicine to cure injuries, sores, herpes, scar tissues, skin problems, frost-bite, and blood purifying. It is primarily used for the treatment due to its numerous pharmacological properties such as analgesic, anti–hyperglycaemic, anti-ulcer, and anti-inflammatory. It is also used to cure gastro-intestinal issues, obstetric issues, eye problems, skin wounds, and some instances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Faradiol, caffeic acid, rutin, and chlorogenic acid isolated from C. officinalis exhibit biological activity [ 162 ]. Pharmacological studies have shown that the marigold exhibits antibacterial, antiviral, anti-inflammatory, antioxidant, hypoglycemic, hypolipidemic, and wound healing properties [ 163 , 164 , 165 ]. In the folk phytotherapy, both C. officinalis and C. arvensis are used as remedies for a wide range of diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Faradiol, caffeic acid, rutin, and chlorogenic acid isolated from C. officinalis exhibit biological activity [ 162 ]. Pharmacological studies have shown that the marigold exhibits antibacterial, antiviral, anti-inflammatory, antioxidant, hypoglycemic, hypolipidemic, and wound healing properties [ 163 , 164 , 165 ]. In the folk phytotherapy, both C. officinalis and C. arvensis are used as remedies for a wide range of diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies show that this plant is rich of polyphenol compounds such as daidzein, genistein, apigenin, quercetin, kaempferol, catechin, resveratrol, curcumin, rutin, betulinic acid, and artemisinin. These compounds can be effective with their anti‐inflammatory, antiangiogenic, and antiproliferative effects on the growth, proliferation, metabolism, function, and motility of tumor cells (Dhanasekaran et al, 2009; Dhingra et al, 2022; Kaur et al, 2019). Quercetin is a flavonoid compound that affects the cell cycle, growth, metastasis, and proliferation of colon, breast, and prostate tumors through various pathways such as p53/miR‐34a/SIRT1, PI3K/AKT/mTOR, IL‐6/STAT3, and Notch/AKT/mTOR and suppresses tumor cells (Lou et al, 2015; Michaud‐Levesque et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that some plant extracts, including Calendula officinalis L., Cassia fistula L., Salmo gairdneri L., Agaricus blazei L., Tinospora cordifolia L., and Punica granatum L., due to their polyphenolic compounds (flavonoids and isoflavonoids), protect hepatocytes against DEN‐induced HCC through different pathways. The extracts of these plants contain different compounds such as daidzein, genistein, quercetin, kaempferol, catechin, resveratrol, curcumin, rutin, betulinic acid, and artemisinin, which suppress various tumors including HCC through anti‐inflammatory, antiangiogenic, and antiproliferative activities (Dhanasekaran et al, 2009; Dhingra et al, 2022; Kaur et al, 2019; Lee & Hong, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the chemical composition of pot marigold seeds (PMSs) has not been fully recognised thus far, whereas the vegetative parts of this plant, especially the flowers, are the most valuable herbal and cosmetic raw material of pot marigold [ 12 ]. Pot marigold extracts from flowers and leaves have broad beneficial effects, of which anti-inflammatory and wound-healing properties are the most documented [ 13 , 14 ]. In contrast to milk thistle, in pot marigold, there is not one specific group of compounds responsible for its beneficial effects, because it contains many groups, including triterpenes, flavonoids, carotenoids, sesquiterpenes and arabinogalactan polysaccharides [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%